Broadband millimeter-wave metasurface antenna array with printed ridge gap waveguide for high front-to-back ratio - Hao Yi; Yajie Mu; Jiaqi Han; Long Li (Journal of Information and Intelligence)
A novel broadband metasurface (MTS) antenna array with high front-to-back ratio (FBR) is proposed for 28 GHz millimeter-wave applications. With slot pairs loaded on patch cells, an aperture-coupled slotted-mushroom MTS antenna is designed to obtain broadband radiation characteristics with a compact size. To suppress the backward radiation of this antenna, the printed ridge gap waveguide (PRGW) technology with a perfect magnetic conductor (PMC) shielding made of mushroom unit-cells underneath the microstrip feeding line is applied. On this basis, a 4 × 4 MTS antenna array with the PRGW feed network is developed. Simulated results show that the FBR can be highly improved by over 16 dB within the entire bandwidth. To validate the design, a prototype of the proposed antenna is fabricated. Measured results show that an FBR greater than 28 dB can be obtained over a 24% impedance bandwidth (from 24.9 GHz to 31.7 GHz) with the reflection coefficient less than −10 dB. The measured antenna gain ranges from 17 dBi to 19.2 dBi and the corresponding measured aperture efficiencies are 35% and 45.6%. The measured results also suggest that the proposed MTS antenna possesses −35 dB cross-polarization level and stable radiation patterns. In addition, the proposed antenna remains a very low profile of 1.7 mm (0.17λ0 at 28 GHz). All the achieved features indicate that the proposed MTS antenna is an important candidate for B5G and 6G wireless communication.